Sustainability Accounting: The Critical Role of Social and Environmental Accounting from Leuit's Perspective in Challenging the Servants of Capitalists - Mujahidi, Khairul; Ramadani, Aulia; Paulina, Elin; Rusdiansyah, Nurul (The Es Accounting And Finance, 2025)
This study delves into the role of Sunda local wisdom, specifically the Leuit, as a representation of social accounting in the traditional Ciptagelar village, Sukabumi. Through an ethnographic approach, the research deeply explores how the Leuit functions as a social accounting system in the lives of the local community. The Leuit, as a traditional rice barn, not only serves as a food storage facility but also symbolizes sustainability and harmony with nature, playing a crucial role in maintaining the community's well-being. Additionally, this study evaluates corporate efforts in environmental preservation through the implementation of Corporate Social Responsibility (CSR) as a form of environmental accounting. A case study was conducted on PT Tirta Investama to assess their CSR contributions towards environmental sustainability and the alignment of these CSR programs with the sustainability principles embodied by the Leuit. By combining ethnographic and case study approaches, this research provides deep insights into social and environmental accounting practices within the context of local wisdom in Ciptagelar Village, as well as the impact of CSR initiatives in the corporate sector. This study aims to offer guidance on integrating traditional values into modern social and environmental accounting practices.